Profile of Ventana ALK (D5F3) companion diagnostic assay for non-small-cell lung carcinomas. (2nd June 2016) - Conde, Esther; Hernandez, Susana; Prieto, Mario; Martinez, Rebeca; Lopez-Rios, Fernando
ABSTRACT: The development of several ALK inhibitors means that the importance of accurately identifying ALK -positive lung cancer has never been greater. Therefore, it is crucial that ALK testing assays become more standardized. The aim of this review is to comment on the recently FDA-approved VENTANA ALK (D5F3) Companion Diagnostic (CDx) Assay. This kit provides high sensitivity and specificity for the detection of ALK rearrangements and seamless integration into the laboratory workflow, with a fully automated analytical phase and fast interpretation. The use of controls increases the sensitivity and specificity and a dichotomous scoring approach enhances reproducibility.